Dye Decolorization and Organic Compounds Removal of Synthetic Textile Effluent (STE) by Anaerobic-aerobic Magnetic Activated Sludge (A2-MAS) Reactor (Plant Tissue Culture and Biotechnology, 2022)
The developed anaerobic-aerobic magnetic activated sludge (A2-MAS) reactor was found to be suitable for the textile effluent management. An azo dye (Orange II) and an anthraquinone dye (Remazol brilliant blue R) were used in the synthetic effluent (STE) for dye decolorization. The A2-MAS reactor consisted of an anaerobic tank (8.0 L) sequenced with an aerobic tank (4.0 L) for simultaneous dye decolorization and organic compounds removal. The anaerobic tank was operated at 35 ± 1°C while the aerobic part was maintained at room temperature. The magnetic separation technique in both aerobic and anaerobic condition of A2-MAS reactor was found effective and it is completely new to anaerobic operation. The sequential A2-MAS reactor attained well with 99.6% dye decolorization and 90.7% CODCr removal with the initial loading of 34.2 mg/l dye compounds and 365 mg/l CODCr, respectively. Anaerobic treatment played the major role for both dye decolorization (96.8%) and CODCr removal (78.4%) for the period of 100 day. Interestingly, sludge emission was zero all throughout the treatment.Plant Tissue Cult. & Biotech. 32(2): 115-125, 2022 (December)